2020
DOI: 10.3390/genes11090988
|View full text |Cite
|
Sign up to set email alerts
|

Exome-Sequence Analyses of Four Multi-Incident Multiple Sclerosis Families

Abstract: Multiple sclerosis (MS) is an inflammatory demyelinating disease of the Central Nervous System (CNS). Currently, it is estimated that 30–40% of the phenotypic variability of MS can be explained by genetic factors. However, low susceptibility variants identified through Genome Wide Association Study (GWAS) were calculated to explain about 50% of the heritability. Whether familial high-risk variants also contribute to heritability is a subject of controversy. In the last few years, several familial variants have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Additionally, class I/II human leukocyte antigen (HLA) genes contribute to an individual’s susceptibility for developing MS. A recent study analysed variants of 16 HLA genes and identified alleles associated with MS risk [ 97 ]. However, similar to other studies, an exome-sequence analysis of four multi-incident MS families did not identify individual disease-causing gene variants [ 98 , 99 , 100 , 101 ]. These results highlight the complex genetic aetiology of MS, and the possibility of a multigenic origin.…”
Section: Application Of Next-generation Sequencing In Neurogenetic Diseasessupporting
confidence: 76%
“…Additionally, class I/II human leukocyte antigen (HLA) genes contribute to an individual’s susceptibility for developing MS. A recent study analysed variants of 16 HLA genes and identified alleles associated with MS risk [ 97 ]. However, similar to other studies, an exome-sequence analysis of four multi-incident MS families did not identify individual disease-causing gene variants [ 98 , 99 , 100 , 101 ]. These results highlight the complex genetic aetiology of MS, and the possibility of a multigenic origin.…”
Section: Application Of Next-generation Sequencing In Neurogenetic Diseasessupporting
confidence: 76%
“…One cannot argue against the contribution of genetic factors to MS susceptibility, as studies regarding the genetics of MS have come a long way in the last few years, and quite a few loci have been unequivocally identified [ 2 , 28 , 29 , 30 , 31 ]. Results from candidate-gene association studies and genome-wide association studies (GWAS) suggest that both common, low-frequency, and rare variants contribute to MS susceptibility [ 4 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the most recently reported WES study of MS, a missense variant in MBP was found in four MS patients from the same family 32 , further pointing towards a role of rare variants in MBP in MS susceptibility. The product of PLK1 is a kinase that phosphorylates and regulates the activity of MTHFR, an enzyme is involved in the synthesis of methionine and its product S-adenosylmethionine (SAM) 49,50 .…”
Section: Discussionmentioning
confidence: 83%
“…This makes multi-incident MS families of interest for identifying and studying rare variants involved in the disease. In the past 10 years, a number of studies have reported rare, putatively pathogenic genetic variants in MS patients from multi-incident families through WES 22,[27][28][29][30][31][32] . Most of these family studies, however, only involved a small number of families, analyses were sometimes targeted exclusively at known MS loci, and the vast majority of the identified variants were not studied in replication studies or did not replicate 27,29,[33][34][35][36] .…”
Section: Introductionmentioning
confidence: 99%